Transient behavior of self-assembled quantum dots formed by atomic layer epitaxy technique - Park, Y.M.; Park, Y.J.; Kim, K.M.; Shin, J.C.; Song, J.D.; Lee, J.I.; Yoo, K.-H. (IEEE International Symposium on Compound Semiconductors, Proceedings, 2003)
We investigated a transient behavior of InGaAs self-assembled quantum dots (SAQD) formed by atomic layer epitaxy technique (ALE). Performing some cycles of InAs/GaAs alternate source supply between InGaAs layers, InGaAs dots-in-a-well structures were spontaneously grown. In order to elucidate the growth mechanism of dots-in-a-well structure, premature SAQD was intentionally prepared by controlling the cycles of source supply. Through the measurement of photoluminescence, not only the discrete quantum well state but also broad emission band was observed, indicating that a mixed structure of QW and QD was existed in a quantum well. The mixed behaviors of the premature QDs were studied in detail using temperature dependence of photoluminescence measurements. ？ 2003 IEEE.